Functional outcomes of upper eyelid blepharoplasty: A systematic review. Issue 2 (February 2019) - Hollander, M.H.J.; Contini, M.; Pott, J.W.; Vissink, A.; Schepers, R.H.; Jansma, J.
Abstract: Objective: Various functional outcomes after upper blepharoplasty are reported in the literature. We systematically reviewed the literature to assess the objective and subjective functional effects of upper blepharoplasty. Methods: After a systematic search of four search engines (Pubmed, Embase, Cinahl and Cochraine), any study on objective and subjective (patient reported) functional outcome after upper blepharoplasty was subjected to a quality assessment for possible inclusion in the review. The intervention was defined as a solitary surgical upper blepharoplasty containing the removal of skin, with or without the removal of a strip of orbicularis oculi muscle and/or upper orbital fat. Eligible studies were randomized controlled trials, controlled trials, cohort studies and case series ( n ≥ 10). Results: A total of 3525 studies were assessed, of which 28 studies were included in this systematic review. Favorable outcomes after an upper blepharoplasty were reported and included enlarged visual field, enhanced quality of life related to fewer headaches and improved vision. Furthermore, sensitivity of the eyelids decreased, with differences in recovery. Outcomes for eyebrow height, astigmatism, contrast sensitivity and eyelid kinematics were not consistent between the studies. No meta-analysis could be performed due to the limited scope of included studies and the great variety in outcomes and blepharoplasty techniques. Conclusions: Upper blepharoplasty is accompanied by a great variety of beneficial functional outcomes including an increased visual field and improvement in headache- and vision-related quality of life. Further research is needed, especially where results are conflicting (effects on eye dryness and eyebrow height) and/or the data are limited (contrast sensitivity, astigmatism).